2004
DOI: 10.1152/ajpheart.01023.2003
|View full text |Cite
|
Sign up to set email alerts
|

Diminished baroreflex control of heart rate responses in otoconia-deficient C57BL/6JEi head tilt mice

Abstract: The maintenance of stable blood pressure during postural changes is known to involve integration of vestibular and cardiovascular central regulatory mechanisms. Sensory activity in the vestibular system plays an important role in cardiovascular regulation. The purpose of this study was to determine the role of vestibular gravity receptors in normal baroreflex function. Baroreflex heart rate (HR) responses to changes in blood pressure (BP) in otoconia-deficient head tilt (het) mice (n = 8) were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
(64 reference statements)
2
13
0
Order By: Relevance
“…The range of normalized CV* values obtained from mice of the present study is comparable to that reported for mouse canal afferents (Lasker et al 2008;Yang and Hullar 2007). The range of CVs as well as the mean CV for the OTO+ data closely approximate those reported in Figure 1 of Yang and Hullar (2007) for "wild-type" C57 mice (no significant difference, p90.2).…”
Section: Resting Discharge Regularity and Rates In Micesupporting
confidence: 89%
See 4 more Smart Citations
“…The range of normalized CV* values obtained from mice of the present study is comparable to that reported for mouse canal afferents (Lasker et al 2008;Yang and Hullar 2007). The range of CVs as well as the mean CV for the OTO+ data closely approximate those reported in Figure 1 of Yang and Hullar (2007) for "wild-type" C57 mice (no significant difference, p90.2).…”
Section: Resting Discharge Regularity and Rates In Micesupporting
confidence: 89%
“…The range of CVs as well as the mean CV for the OTO+ data closely approximate those reported in Figure 1 of Yang and Hullar (2007) for "wild-type" C57 mice (no significant difference, p90.2). Moreover, there is no significant difference in the distribution of CV-ISI pairs obtained from normal mice of the two studies (i.e., OTO+ mice in the present study and C57 wild-type mice; Yang and Hullar 2007; chi-square, p=0.1).…”
Section: Resting Discharge Regularity and Rates In Micesupporting
confidence: 80%
See 3 more Smart Citations